Effect of folic acid on animal models, cell cultures, and human oral clefts: a literature review (2020)
Background Folate is a naturally occurring, water-soluble B vitamin. The synthetic form of this compound is folic acid (FA), the deficiency of which is linked to neural tube disorders (NTD), which can be prevented by consuming it before, or during the early months of, pregnancy. However, the effect of FA on oral cleft formation remains controversial. The aim of the present study was to review the evidence concerning the effect of FA on the formation of cleft lip and palate (CLP) in both animals and humans, as well as its impact on different cell types. A search was conducted on various databases, including MEDLINE, EMBASE, and Central, for articles published until January 2020. Main body Current systematic reviews indicate that FA, alone or in combination with other vitamins, prevents NTD; however, there is no consensus on whether its consumption can prevent CLP formation. Conversely, the protective effect of FA on palatal cleft (CP) induction has been inferred from animal models; additionally, in vitro studies enumerate a cell-type and dose-dependent effect of FA on cell viability, proliferation, and differentiation, hence bolstering evidence from epidemiological studies. Conclusions Meta-analysis, animal models, and in vitro studies demonstrated the protective effect of FA against isolated CP; however, the heterogeneity of treatment protocols, doses, and FA administration method, as well as the different cell types used in in vitro studies, does not conclusively establish whether FA prevents CLP formation.